2019
DOI: 10.1080/24699322.2018.1560096
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgical techniques for the therapy of far lateral disc herniation in middle-aged and elderly patients

Abstract: Xiang (2019) Minimally invasive surgical techniques for the therapy of far lateral disc herniation in middle-aged and elderly patients,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Fifteen patients diagnosed with FLLDH underwent PELD in the study conducted by Liao et al [10] gained an overall excellent and good rate of 93.3%. Ren et al [21] concluded that PELD had a shorter operation time and less surgical trauma, being a less invasive and more economical method for middle-aged and elderly FLLDH patients. A research conducted on 22 patients with FLLDH at the L5-S1 level and treated by PELD also revealed that overall excellent or good outcomes were 81.8 % [22].…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen patients diagnosed with FLLDH underwent PELD in the study conducted by Liao et al [10] gained an overall excellent and good rate of 93.3%. Ren et al [21] concluded that PELD had a shorter operation time and less surgical trauma, being a less invasive and more economical method for middle-aged and elderly FLLDH patients. A research conducted on 22 patients with FLLDH at the L5-S1 level and treated by PELD also revealed that overall excellent or good outcomes were 81.8 % [22].…”
Section: Discussionmentioning
confidence: 99%
“…Far-lateral lumbar disc herniation (FLLDH) is a rare disease that accounts for 2-12% of all lumbar disc herniation syndromes, and it was first described by Abdullah in 1974 [1] . With increased awareness of the disease, experts have paid increasing attention to the diagnosis and treatment of FLLDH [2,3] . The resulting nerve root syndrome is characterized by intense pain, often accompanied by motor or sensory disturbances [3] .…”
Section: Introductionmentioning
confidence: 99%
“…With increased awareness of the disease, experts have paid increasing attention to the diagnosis and treatment of FLLDH [2,3] . The resulting nerve root syndrome is characterized by intense pain, often accompanied by motor or sensory disturbances [3] . The diagnostic probability of FLLDH increases with the use of computed tomography (CT) and magnetic resonance imaging (MRI) [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Far-lateral lumbar disc herniation (FLLDH) is a rare disease that accounts for 2-12% of all lumbar disc herniation syndromes, and it was rst described by Abdullah in 1974 [1] . With increased awareness of the disease, experts have paid increasing attention to the diagnosis and treatment of FLLDH [2,3] . The resulting nerve root syndrome is characterized by intense pain, often accompanied by motor or sensory disturbances [3] .…”
Section: Introductionmentioning
confidence: 99%
“…With increased awareness of the disease, experts have paid increasing attention to the diagnosis and treatment of FLLDH [2,3] . The resulting nerve root syndrome is characterized by intense pain, often accompanied by motor or sensory disturbances [3] . The diagnostic probability of FLLDH increases with the use of computed tomography (CT) and magnetic resonance imaging (MRI) [4] .…”
Section: Introductionmentioning
confidence: 99%